Fine-structural alterations and clustering of developing synapses after chronic treatments with low levels of NMDA - Yen, LH (J Neurosci, 1993)
In the visual pathway of frogs it is possible to apply low levels of NMDA chronically to the optic tectum and study the mechanisms underlying the stabilization of synapses developing within the CNS. Earlier studies (Cline and Constantine-Paton, 1990) found that chronic NMDA treatment of tecta innervated by two retinas results in a reduction of branching within the terminal arbors of retinal ganglion cells (RGCs). We now report that this same chronic NMDA treatment produces fine-structural changes in synaptic morphology as well as local synaptic rearrangements within the retinotectal neuropil. Chronic NMDA treatment of doubly innervated tecta was associated with a thickening or darkening of both pre- and postsynaptic densities. These changes in synapse morphology were restricted to the superficial neuropil of tecta in regions where reductions in branches of RGC axonal arbors were observed at the light microscopic level. The fine- structural effects were absent from similarly treated tecta innervated by only one eye, where RGC axonal arbor pruning was not observed. Stereological analyses indicated that the incidence of two or more presynaptic profiles converging on the same postsynaptic process was significantly increased in the NMDA-treated, doubly innervated tecta. This observed increase in synaptic clustering was not associated with a larger synaptic active zone, or with an increase in the number of synapses per unit volume. These data are discussed in the context of the hypothesis that chronic NMDA treatment raises the threshold for synapse stabilization in tectal neurons, causing the selective loss of poorly correlated synapses of both retinal and non-retinal origin from tectal neuropil that is innervated by two retinas: increased pre- and postsynaptic thickening could reflect greater efficiency in the remaining synaptic contacts and their closer spatial proximity on the same postsynaptic process is consistent with greater cooperativity and less competition.